Exploring parents' reasons for attending the emergency department for children with minor illnesses: a mixed methods systematic review. Issue 1 (2nd November 2018) - Butun, Ahmet; Linden, Mark; Lynn, Fiona; McGaughey, Jennifer
Abstract : Background: The number of EDs visit is on the increase, and the pressure on EDs is of significant concern worldwide. The usage of EDs by parents of children with minor illness is an important and still unresolved problem causing a burden to healthcare services. The aim of this study was to review the literature to summarise parental reasons for visiting ED for children with minor illness. Method: Seven electronic databases (Medline, Embase, PsycINFO, CINAHL, PubMed, Web of Science and Scopus) were comprehensively searched during a 2-week period in August 2016 and updated between 11 and 20 June 2018. The study selection process was undertaken independently by two authors. Qualitative and quantitative studies that focused on the reasons for parents of children with minor illness to attend an ED were included. Studies were assessed for quality and data were analysed by means of narrative synthesis. Results: Twenty-four studies were included. Eleven studies employed quantitative methods, eleven studies used qualitative methods and two studies used mixed methods. Parental reasons for using ED included perceived urgency, ED advantages (eg, faster service, superior ED resources and efficiency), difficulties with getting a general practitioner appointment, lack of facilities in primary healthcare services, lack of health insurance, reassurance, convenience and access. Conclusion: This review identified some of the reasons why parents bring their children to the ED for minor illnesses highlighting the multifaceted nature of this problem. Understanding parental reasons behind their choice to use the ED may help us better design targeted interventions to reduce unnecessary ED visits and alleviate the burden on overstretched healthcare services. This review may help inform emergency care policy makers, researchers and healthcare staff to understand parents' reasons for visiting the ED, to better meet their healthcare needs.